Italy : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper analyzes the competitiveness and wage bargaining reform in Italy. The growth of Italian exports has lagged that of euro area peers. Wages are set at the sectoral level and extended nationally. However, they do not respond well to firm-specific productivity, regional disparities, or skill mismatches. Nominally rigid wages have also implied adjustment through lower profits and employment. The analysis also suggests substantial gains from moving from sectoral- to firm-level wage setting of at least 3.5 percentage points, lower unemployment (or higher employment) rate and a notable improvement in Italy's competitiveness over the medium term.